Trust as a booster - Reiersen, Jon (Journal of Business Economics and Management, 2017)
In his book Trust. The Evolutionary Game of Mind and Society, social psychologist Toshio Yamagishi (2011) states that trust can be viewed as a “booster rocket” that provides the necessary push for the take-off from the secure ground of committed relations. This article formalizes this idea with the help of a simple game theoretic model. The article looks at a situation where networks of personalized exchange relationships provide assurance against untrustworthy behaviour but reduce the opportunity to profit from trade in larger markets. Assuming that the anonymous market contains both trustworthy and untrustworthy types, it is demonstrated that mutual trust relations can emerge, even when there is a clear danger of opportunism and the possibility of repeated interaction is ruled out. From a more practical perspective, the model provides an insight into the role trust plays for the decision to transact in networks or markets. It is also demonstrated that networks appear as mixed blessings. Networks reduce the problems arising from incomplete contracts and behavioural risk, but they also restrict individuals’ possibility to reap potential gains produced in larger markets.